PENGGUNAAN MODEL RAD UNTUK PEMBANGUNAN SISTEM INFORMASI PENJUALAN TIKET BUS ONLINE - Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2014)
Daily activities PO Bus today still use the conventional system in booking tickets, the passengers came agencies Sales bus ticket and booked a ticket in accordance with the schedule provided and the number of seats desired or booked over the phone which will then be recorded in book reservations. This manual system, the company must provide a place or an office used to receive and record passengers who will book the tickets and must always be available employees to accept the ticket booking. Companies need a system that is more practical, efficient and accessible to everyone from everywhere to facilitate passengers in ticket reservations. The purpose of this study to make it easier for passengers in booking tickets, and simplify the recording of ticket reservation which in turn can increase the productivity and efficiency of time and place. The development model systems used RAD Model.